Analysis of merging polar-front and subtropical jet streams and its effect on rainfall in western Iran from December 12 to 15, 2010 - Aida Faroghi; Manuchehr Farajzadeh (تحقیقات کاربردی علوم جغرافیایی)
In this study, the frequency of merging events between the polar-front jet stream and the subtropical jet stream, along with their impact on precipitation patterns in western Iran, was analyzed over a ten-year statistical period (2010–2019). Utilizing coding in GrADS, 300 hPa jet stream maps were produced at six-hour intervals. Throughout the study period, the axes of these two jet streams merged on several occasions.